Prevalence of SARS-CoV-2 in residents of Divinópolis, MG: experience report (Research, Society and Development, 2021)
The objective was to describe the experience of the interviewers of the project “Prevalence of SARS-CoV-2 in Residents of Divinópolis – MG”, as well as the perception of Basic Health Units during the pandemic period. As a methodology, the experience report of academics in the field of collection and the perception of the functioning of the Basic Health Units (UBS) during the new coronavirus pandemic were proposed. From this experience, the results showed the importance of training interviewers, the impact of the outdated Health Information System (SIS), the need to restructure the methodology, the use of saliva collection to the detriment of the nasal swab, the importance of the database. Data, as well as the partnership between the Public University and the Municipal Health Department. It was concluded that participating in the research increased knowledge about COVID-19 and fostered student satisfaction and self-confidence in relation to professional development. The possibility of knowing the functioning of the PHC in the municipality is highlighted, as well as contributing to the construction of public policies to combat the disease.